Mode-locked thulium ytterbium co-doped fiber laser with a graphene saturable absorber - Babar, I.M.; Paul, M.C.; Das, S.; Dhar, A.; Ahmad, Harith; Harun, Sulaiman Wadi (Photonics Society of Poland, 2016)
A passively mode-locked Thulium Ytterbium co-doped fiber laser (TYDFL) is demonstrated using a graphene polyvinyl alcohol saturable absorber as the mode-locker. With 980nm multimode pumping, the laser operates at 1942.95nm with repetition rate of 11.76MHz. The pulse width is calculated to be around 52.85ps. The maximum pulse energy of 1190.5pJ is achieved at pump power of 1750mW.